Students Listening Skill Through Discovery Learning Model Using English Preparation Test - Syaprizal, Syaprizal; Arono, Arono; Yunita , Wisma (Proceeding International Conference on Malay Identity, 2024)
This research aims to determine whether or not a discovery learning model can be used for third- semester UNPARI English study program students using an English preparation test. The researcher used a pre-experimental design with one group pre-test and post-test in this study. This study's population and sample were semester students, with a total of 23 students in the sample. Simple random sampling was used to select the sample for this study. To collect data, the researcher administered a multiple-choice test to the students twice (pre-test and post-test). The researcher used the data to analyze individual scores, normality testing, and the matched t-test formula. The pre-test mean score was 67.30, and the post-test mean score was 86.13. obtained was 9.76 and the table was 2.069. The alternative hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. Therefore, teaching listening skills through the discovery Learning Model using the English Preparation Test to the third-semester English students was effective.